Allowing for uncertainty in exogenous shocks to CGE models: the case of a new renewable energy sector. Issue 4 (2nd October 2017) - Phimister, Euan; Roberts, Deborah
ABSTRACT: The paper explores the importance of allowing for uncertainty in the magnitude of exogenous shocks in Computable General Equilibrium (CGE) models. The shock examined is the introduction of a new onshore wind sector in North East Scotland. A simple analytical model is developed to show how, a priori, the size of the new sector (the model shock) is uncertain and asymmetrically distributed as a result of spatial correlation in costs and returns across potential development locations. The importance of allowing for this uncertainty is tested by comparing the results from a CGE model where the sector size is assumed known with certainty to those from a model where the sector size is a random variable with an asymmetric distribution. The results show the extent to which allowing for uncertainty can influence the magnitude of estimated impacts with some variables more sensitive to the uncertainty than others.